Diagnostic significance of combining D-dimer with high-sensitivity cardiac troponin I for improving the diagnosis of venous thromboembolism in the emergency department: Troponin for diagnosing venous thromboembolism - Bonfanti, Laura; Cervellin, Gianfranco; Calamai, Simone; Lunian, Marco; Aloe, Rosalia; Lippi, Giuseppe (Acta Biomedica Atenei Parmensis, 2021)
Background. Although cardiac troponins are valuable tools for risk stratification in patients with venous thromboembolism (VTE), their significance remains elusive in diagnosing venous thrombosis. Methods. D-dimer (age-adjusted cut-off) and high-sensitivity cardiac troponin I (HS-cTnI; reference limit,